Stigma and Discrimination of People with HIV/AIDS by Health Officers in Bulukumba Regency - Suswani, Andi; Haerati, Haerati; Asri, Asri; Safruddin, Safruddin; Amalia, Andi Risky (Global Medical & Health Communication (GMHC), 2023)
Stigma and discrimination against people with human immunodeficiency virus/acquired immune deficiency syndrome (HIV/AIDS) are among the biggest obstacles to preventing and overcoming (HIV/AIDS) in Indonesia. This study aims to analyze the factors related to stigma and discrimination and determine the types of stigma and discrimination given by health workers to people with HIV/AIDS. The population in this study were health workers in 20 health centers in Bulukumba, consisting of nurses, midwives, health analysts, doctors, and public health. The sampling technique used a total sampling of 322 health workers, and data was collected online through Google Forms on 15–26 February 2021 and analyzed univariately and bivariate using the chi-square and linear association tests. The results showed that type of profession (p=0.041) and knowledge (p=0.019) were factors related to stigma and discrimination. The most considerable stigma experienced by people with HIV/AIDS was feeling disgusted and uncomfortable being around people with HIV/AIDS, and the notion that HIV/AIDS disease suffered was only the result of free sex. At the same time, discrimination was a form of the biggest problem was the behavior of health workers who will use layered handsome when performing/providing services to people with HIV/AIDS.